STUDI KOMPARASI ANTARA DEMONSTRATION DAN DISCUSSION PADA PENGUASAAN KEMAMPUAN MENULIS MAHASISWA - Testiana Deni Wijayatiningsih; Anggarani Wilujeng (Universitas Muhammadiyah Semarang, 2014)
This research is based on the lack of students’capability in composing sentences to be meaningful text. This condition can be seen from the students’writing score which is relative low and their writings are lack of coherence and cohesion. Based on this problem, the reseacher creates interesting innovation for the teaching learning process by using demonstration and discussion method. The objective of the research is how to compare between demonstration and discussion to improve students’writing skill statistically. It uses demonstration and discussion inwhich students’writing were compared significantly using t-test formula for analyzing the data.The result shows that there is a significant difference between making use of demonstration and discussion. The students’score of writing taught by discussion are better than those taught using demonstration method. It is also supported by students’questionaire. Finally, the researcher encourages lecturers not only to use interactive media, method, or technique but also support students’ to learn how to write well writing.